FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA KARYAWAN - Yupiter Gulo (Jurnal Bisnis dan Akuntansi, 2012)
The purpose of this research is to examine the effect of job satisfaction with three variables that influence the transformational leadership, communication and work environment. The method which is used in this research is the method of causality. Respondents involved in this research as many as 103 employees. This research uses purposive sampling technique. The data collection was done by distributing questionnaires. And the method for data analysis in this research is multiple linear regression . The result of this research is positive influence of transformational leadership, communication, and work environment to employee job satisfaction.